What determines employee procrastination and multitasking in the workplace: personal qualities or mismanagement? - Vveinhardt, Jolita; Sroka, Włodzimierz (Journal of Business Economics and Management, 2022)
The nature of procrastination is usually analysed from the angle of the psychological mechanism, in the aspects of demotivating factors; however, there are not many studies emphasizing procrastination provoked by mismanagement. A similar situation is also observed with regard to multitasking analysed in this article, which is recorded at work not because employees naturally like to multitask but because they have no other way out. The purpose of this article is to present the results of the empirical study revealing the nature of procrastination and multitasking in the workplace. The study involved 995 employees of Polish (N = 500) and Lithuanian (N = 495) private sector organizations. It has been found that a share of employees are forced to become procrastinators and multitaskers due to management flaws. In addition, procrastination and multitasking are related by medium strength statistical relationships, regardless of the country. The value of the research is presupposed by the fact that it presents new and original data showing the situation of multitasking and procrastination in Lithuanian and Polish organizations. These results improve the literature on procrastination by providing additional confirmatory evidence on how more flexible work organization can serve for better understanding of causes of multitasking and procrastination.First published online 28 February 2022